2009
DOI: 10.1007/s12264-009-0416-3
|View full text |Cite
|
Sign up to set email alerts
|

Rottlerin protected dopaminergic cell line from cytotoxicity of 6-hydroxydopamine by inhibiting PKCδ phosphorylation

Abstract: Objective The present study aims to investigate the role of protein kinase C δ subtype (PKCδ) phosphorylation in the process of 6-hydroxydopamine (6-OHDA)-induced dopaminergic cell death, and demonstrate the molecular basis of neurological disorders, such as Parkinson's disease. Methods The pheochromocytoma (PC12) cell line was employed in the present study. Cells were treated with 2 μmol/L PKCδ inhibitor Rottlerin, 10 nmol/L protein kinase C α subtype (PKCα) inhibitor bisindolylmaleimide I, or 5 nmol/L Gö6976… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…We also examined whether the increased SDC2 expression in suspended melanoma cells was also mediated by PKCδ activation. Specific inhibitor on PKCα/β, Gö6976 [ 28 ], and inhibitor on PKCδ, Rottlerin [ 28 ], were used to treat cells and the level of SDC2 expression was characterized by qPCR. As seen in Figure 2 , PKCα/β inhibitor, but not PKCδ inhibitor, reduced SDC2 expression in adherent melanoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…We also examined whether the increased SDC2 expression in suspended melanoma cells was also mediated by PKCδ activation. Specific inhibitor on PKCα/β, Gö6976 [ 28 ], and inhibitor on PKCδ, Rottlerin [ 28 ], were used to treat cells and the level of SDC2 expression was characterized by qPCR. As seen in Figure 2 , PKCα/β inhibitor, but not PKCδ inhibitor, reduced SDC2 expression in adherent melanoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation statues of PKCδ have been suggested to play a critical role in determining its functional properties [34,35,38]. For example, the catalytic activity of membrane-associated allosterically activated PKCδ is increased by its Thr505 phosphorylation [34][35][36][37]. The impact of wogonin on PKCδ phosphorylation is dependent on cell types and their physiological or pathophysiological condition.…”
Section: Discussionmentioning
confidence: 99%
“…firstly examined the impact of wogonin on PKCδ phosphorylation at Thr505 residue, which reportedly increases the catalytic activity of membrane-associated allosterically activated PKCδ [34][35][36][37]. Mature 3T3-L1 adipocytes were starved serum for 4 h and then treated with 5 μmol/L, 10 μmol/L, 20 μmol/L of wogonin for 24 h, or 10 μmol/L of wogonin for 6 h, 12 h, or 24 h. The cells treated with 10 μmol/L PKCδ specific inhibitor rottlerin for 24 h serviced as positive controls, because it has been shown to inhibit both PKCδ phosphorylation and its action [37].…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…After this initial publication, it was reported that Rottlerin is ineffective at directly inhibiting PKCδ activity but likely inhibits the enzyme by an indirect mechanism via ATP depletion, reactive oxygen species generation and altering PKCδ tyrosine phosphorylation (Soltoff, 2007). Additional studies have demonstrated, however, that Rottlerin does decrease PKCδ activity (Chaudhuri et al, 2005; Fan et al, 2006; Fan et al, 2009). In addition, treatment of various neuronal cell types with Rottlerin results in data comparable to that of the same neuronal cell types treated with dominant negative PKCδ (Zhang et al, 2007), neurons from PKCδ knockout mice (Zhang et al, 2007; Zhang et al, 2009), PKCδ-small interfering RNA (Zhang et al, 2007) or catalytically inactive PKCδK376R (Kanthasamy et al, 2008) supporting the assertion that Rottlerin inhibits PKCδ activity.…”
Section: Discussionmentioning
confidence: 99%